Sleep and fatigue management strategies: How nurses, midwives and paramedics cope with their shift work schedules-a qualitative study - Lauren A. Booker; Jarrah Fitzgerald; Jane Mills; Melanie Bish; Jo Spong; Melissa Deacon‐Crouch; Timothy C. Skinner (Wiley, 2024)
Abstract Aims To understand the benefits and challenges of shift work, and the coping strategies used by nurses, midwives and paramedics to manage the impact of shift work on sleep and fatigue from shift work. Design A single case study with embedded units. Methods Twenty‐seven participants were interviewed exploring their shift work experiences, coping strategies used to improve sleep, and what their recommendations are for improving shift work management. Interviews were completed between November and December 2022. Results Participants enjoyed the lifestyle, flexibility and financial rewards offered by working shift work. However, fatigue and sleep deprivation undermined these benefits, as it impacted their ability to enjoy social and family events. There were also concerns of long‐term health consequences of shift work and delivery of care. Changes to rostering practices and sleep and shift work education were common recommendations. Conclusion This study provides insights on how healthcare professionals manage sleep and fatigue due to shift work and the inadequate support. There is absence of adequate policies, processes and training at an organizational, academic and personal level on how to best manage sleep and fatigue when working shift work. Future research is needed to explore how to equip healthcare shift workers with the skills to successfully manage their schedules to mitigate the negative impact that poor sleep and fatigue has on the health and safety of themselves and their patients. Implications for the Profession and/or Patient Care Understanding the specific challenges of shift work and how workers manage their shift work schedules is critical for improving the health and safety of themselves and their patients. This study identified that there is insufficient training regarding sleep and shift work management strategies, potentially leading to occupational health and safety concerns. Further education and training to equip staff with the necessary information, training and guidance to staff on how to reduce fatigue risk is required. Patient or Public Contribution This study involved healthcare shift workers in semi‐structured interviews. Data gathered from a previous survey that participants were involved in helped shape the interview topics and the study design.